Litter Dynamics of Two Oak Species (Quercus leucotrichophora and Q. Floribunda) in Garhwal Himalaya - Dhaulakhandi, Manoj; Rajwar, Govind S. (Indian Forester, 2005)
Quercus leucotrichophora and Q. floribunda were two important tree species of the montane zone of Garhwal Himalaya. Total litter production of Quercus leucotrichophora (site I) forest was estimated as 663.9Â±56.8 gm-2 yr-1 and Q. floribunda (site II) forest as 564.1 Â± 27.74 gm-2 yr-1. Leaf fall contribution to the total litter fall was 530.0 Â± 50.1 on site I and 446.0 Â± 25.7 gm-2 yr-1 on site II. The litter decomposition rate on both the sites was maximum in August. Total litter decomposition after a period of 13 months on site I was 75.1 and on site II 66.6 %. Decomposition constant (K’) values for these species were 0.75 and 0.67 respectively.